Integration of Clinical Supervision and Behavior in Improving the Quality of Teaching and Student Behavior in Educational Institutions - Amarullah, Mohammad Syarifuddin; Alifiyah, Nur; Gunawan, Agus; Supardi, Supardi (Formosa Journal of Science and Technology, 2024)
Quality education is the key in forming individuals who have maximum potential to face life's challenges. In the 2003 National Education System, education is a conscious and planned effort to create a learning atmosphere that can develop students' potential optimally. This study aims to explore the integration of clinical superviso and behavioural approaches in improving the quality of teacher teaching and student behavior in educational institutions. The research method used is qualitative with a case study approach at MI Daarul Ilmi, Tangerang Regency. The results of the study show that the integration of clinical supervision and behavior approach has a positive impact on improving the quality of teaching and student behavior. Supervise clinics improve teachers' ability to manage learning in a more creative and effective way, while behavioral approaches help create a conducive classroom environment.